2009
DOI: 10.1007/s11274-009-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Fungal selectivity of two mycorrhiza helper bacteria on five mycorrhizal fungi associated with Pinus thunbergii

Abstract: The fungal selectivity of helper effect was revealed using four ectomycorrhizal fungi (Rhizopogon sp., Pisolithus tinctorius, Cenococcum geophilum and Suillus granulatus), and one ectoendomycorrhizal fungus (Wilcoxina mikolae). Previously, we isolated a rhizobacteria, Ralstonia basilensis and Bacillus subtilis, which have the ability to enhance the mycorrhizal symbiosis between S. granulatus and Pinus thunbergii. However, the characteristics of each bacterium on mycorrhizal fungi are still unclear. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, mycelium inoculum has been shown ineffective in producing mycorrhizal seedlings with other EMMs. Kataoka et al (2009) also confirmed that MHB strains of Ralstonia basilensis and Bacillus subtilis are fungal selective when tested with four ECM fungi including EMM fungi Rhizopogon sp. Diáz et al (2009) studied on the production of saffron milk cap mycorrhised Pinus halepensis seedlings under nursery conditions.…”
Section: Chapter 15supporting
confidence: 60%
“…However, mycelium inoculum has been shown ineffective in producing mycorrhizal seedlings with other EMMs. Kataoka et al (2009) also confirmed that MHB strains of Ralstonia basilensis and Bacillus subtilis are fungal selective when tested with four ECM fungi including EMM fungi Rhizopogon sp. Diáz et al (2009) studied on the production of saffron milk cap mycorrhised Pinus halepensis seedlings under nursery conditions.…”
Section: Chapter 15supporting
confidence: 60%
“…Various hypotheses have been proposed to explain the mechanistic basis for the bacterial mycorrhiza-helper effect (15,186). An understanding of the basis of mycorrhizal helper bacteria specificity will aid the selection of the best strains for application in crop plants to enhance mycorrhization and may provide insight into BFIs beyond those found in the context of mycorrhizas.…”
Section: Influence On Host Nutritionmentioning
confidence: 99%
“…Mycorrhizas (-fungus-roots‖) are symbiotic associations between specialized soil fungi and plants, and represent one of the many specialized members of micro-organisms that inhabit the rhizosphere. These include N-fixing symbioses including rhizobia and Actinomycetes and other specialized bacteria such as mycorrhiza helper bacteria [6][7][8][9]. Functionally, this group of fungi has evolved along with their plant-hosts (Table 2) and display a variety of ways in which they interact with both readily and poorly available nutrient resources.…”
Section: Natural History and Evolutionary Settingmentioning
confidence: 99%